Researches of modern development of business environment in Ukraine - Grinko, Alla; Hrynko, Pavlo (Technology audit and production reserves, 2017)
The article deals with concept of «business environment». The views of scientists on its essence are analyzed and definition as an integrated set of objective and subjective various external and internal factors is suggested that mediate business relations and allow the entrepreneur to succeed in realization of objectives, in the implementation of business projects and contracts at a profit. Article describes the dynamics of basic indicators of business development in Ukraine (the number of small businesses, the number of employed in small business and the volume of sales). Conceptual provisions of development of entrepreneurial relations that are the basis of author's interpretation of essence, goals and functions of business management are presented.